Zakat Profesi Langkah Cerdas Mengatasi Kesenjangan Dan Pemicu Pertumbuhan Ekonomi Indonesia (ZISWAF: Jurnal Zakat dan Wakaf, 2018)
The government continues to try to boost the rate of economic growth. By the Jokowi government, the growth target must reach 7 percent in 2018. But what hand power does not arrive. Our growth rate is only around 5 percent. Of course this is a challenge for the government. Until the last 3 years, the rate of economic growth has not been significantly increased. Likewise the poverty rate. Although there was a decrease according to the 2017 BPS report, it was not significant. Various efforts made by the government include utilizing the potential of professional zakat in Indonesia. The potential of zakat in Indonesia is so great. The potential zakat statistics have experienced tremendous increases. Even by BAZNAS, it is said that in 2017, the potential of zakat in Indonesia reaches 217 trillion rupiah. Likewise some research results indicate this potential. This also makes the international world, especially Middle Eastern countries, positively appreciate the handling of zakat in Indonesia. But the huge potential of zakat has not been directly proportional to the realization of zakat receipts. This is what the Indonesian government must be serious about by maximizing the zakat institutions optimally.